Phraseological Units in “The Captain’s Daughter” by Alexander Pushkin: Chinese Translations and Comments - J. Tong (Научный диалог, 2017)
The problem of translation of Russian phraseological units into Chinese is covered. It is noted that idioms, being a common means of artistic expression, at the same time constitute one of the obstacles to translation of literary texts from Russian into Chinese because of the differences in cultures, history and traditions of the two countries. The question is raised about distinguishing the terms “idiom,” “proverb,” “saying” by Chinese linguists and translators. The results of a comparative analysis of some Russian phraseological units and their translation into the Chinese language are presented, extracted from seven editions of the novel “The captain’s Daughter” by Alexander Pushkin. The research urgency is caused by the fact that phraseological units are one of the indicators of the richness of the language of the author of a literary text, elements of the author’s style, that is why professional translations need to preserve means of the style of the artwork. Novelty is determined by the absence of studies of translations of A. S. Pushkin both among Russian and Chinese linguists. It is noted that translators differ in their attitude towards the need to comment the author’s expressions for Chinese readers. Language material of this article is limited by phraseology which is commented in translated editions. Special attention is paid to phraseology, which incorrect translation may hinder understanding of a literary text by the reader - foreign student.